Peranan Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) dalam Memberikan Perlindungan Hukum Terhadap Perempuan dan Anak Korban KDRT - Dona Fitriani; Haryadi Haryadi; Dessy Rakhmawati (PAMPAS: Journal of Criminal Law, 2021)
The objectives of this study are: to determine implementation of the role of the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) providing legal protection for women and children victims of domestic violence (KDRT). To find obstacles providing legal protection for women and children for being victims. Research Method: The method used is Juridical Empirical. Research Results: 1)Role’s implementation of the P2TP2A in Muaro Jambi providing legal protection for women and children by providing socialization, then implementing the Law of Child Protection and Law of Republic Indonesia of Elimination of Domestic Violence. 2)Obstacles experienced by P2TP2A Muaro Jambi providing legal protection for women and children. Namely, not having a safe house, limited budget, lacking human resources, many people who do not understand the law, victims and their families are not open in providing information, withdrawal of complaints from the police, P2TP2A Muaro Jambi lacks psychologists. Suggestion: The government should cooperate with P2TP2A in Muaro Jambi dealing with KDRT’s case and the community should be give more understanding regarding domestic violence’s law.   ABSTRAK Penelitian ini bertujuan untuk mengetahui pelaksanaan peranan Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kabupaten Muaro Jambi dan kendalanya dalam memberikan perlindungan hukum terhadap perempuan dan anak korban KDRT. Tipe penelitian ini adalah Yuridis Empiris. Hasil penelitian adalah pelaksanaan peranan P2TP2A Kabupaten Muaro Jambi dengan memberikan sosialisasi, penerapan Undang-Undang Tentang Perlindungan Anak dan Undang-Undang Tentang Penghapusan Kekerasan Dalam Rumah Tangga. Sedangkan kendala yang dialami yaitu tidak mempunyai Rumah Aman, anggaran yang terbatas, SDM  yang kurang, masyarakat yang kurang paham dengan hukum, korban dan keluarga tidak terbuka dalam memberikan keterangan, penarikan pengaduan dari pihak Kepolisian dan kekurangan psikolog. Saran: diharapkan pemerintah dapat bekerjasama dengan baik dengan P2TP2A Kabupaten Muaro Jambi dalam menangani kasus KDRT dan masyarakat diberikan pemahaman hukum mengenai KDRT.